Estudio de mercado para la creación de una procesadora de cacao en el cantón Santa Rosa provincia de El Oro - Pacheco Medina, José Manuel (2012)
Cocoa is one of the most important items in the canton of Santa Rosa, so that this strength has been a possibility of development, as there is in the canton a company engaged in cocoa processing, based on this premise has seen the need to do this work. For this study had the following objectives: 1. Conduct a market study, 2. Establish the viability of the company according to factors such as transportation, raw material availability and location of customers, 3. Design the organizational and management structure for the company, 4. Assess financial and socio-economic feasibility for market launch of a processing plant.This study resulted in the project is feasible and profitable, thus reducing costs allowing lower the price you are offering the product. The administration and organization of the company was responsible for cocoa farmers who are targeted by this project. Financially the project is accepted by being in front of an IRR of 103% and 14.68% of AARR portion comprising at market research work was done in an exploratory way, to analyze the feasibility of the project, we used the analysis model incremental flow.The study led to the discovery that direct competition for entrepreneurship are the marks M & M, Toblerones, Lindtt, since the path they have in the market have optimized its process technology, the best way forward in the implementation is to make a bank loan since the projection indicates that the first year and then recoups its investment earnings will be increased year by year. There is a high bargaining power to cover subsequent markets, and these are guaranteed, since the price governs the commodity market, but locally, there is oligopoly in industries such as Nestle and Confiteca.